Idea kolegialnej władzy wykonawczej - ŻYROMSKI, Marek (Przegląd Politologiczny, 2018)
Montesquieu’s idea of the tripartite system already expressed a concern with preventing one power from dominating excessively. Another argument for the collegial nature of power is the concern with the continuation of state authorities at the time of crisis (e.g. the tragedy in Smoleñsk). The idea of collegial executive power emerged already in antiquity as evidenced by the two kings in Sparta, the collegiums of archons in Athens, two consuls in the Roman Republic, or the system of tetrarchy, initiated by Diocletian. At present we have the ‘rotating presidency’ in Bosnia or the French principle of ‘cohabitacion’.